Analysis of the Factors Affecting Material Management in Selected Hydropower Construction Projects in Nepal - Maharjan, Binod (Everest Advances in Science and Technology, 2025)
The main goal of this research is to identify the most influencing factors that are affecting material management system in under construction hydropower projects in Nepal. Material management in hydropower construction projects is one of the important issues of Nepal with costing around NRs. 500 to 600 billion considering 50% to 60% of total cost of hydropower construction projects. As of fiscal year 2018-19, hydropower projects with total capacity of 4642 MW are already under construction. Material mismanagement in hydro projects could cause huge amount of nation’s capital to be expensed on unproductive cost overrun caused due to delays. A total of 15 under construction hydropower projects are taken as the study area for data collection. The respondents are requested to rank their answers in five-point Likert scale. The responses for total numbers of 34 factors categorized into 10 headings viz. Planning, Supplier, Finance, Staff, Transport, Storage and Handling, Management, Contractual Issue, Governmental Interference and Environment / Weather are collected. The factors are then ranked using Relative Importance Index technique. Based upon the responses, material requirement planning under planning group is ranked as most influential factor affecting material management system. Based upon the study, it is concluded that most of the hydro projects are using Enterprise Resource Planning software viz. tally and other third-party software for material management and some of them are using Microsoft Excel. Most of the studied hydropower construction projects are located at remote areas where facilities of electricity from national power grid, internet facility is unavailable. Because of this, material requisition is still executed using phone conversation in some projects. Record keeping is still paper based rather than digital method.